The Impact of Endoplasmic Reticulum-Associated Protein Modifications, Folding and Degradation on Lung Structure and Function - Nakada, Emily M.; Sun, Rui; Fujii, Utako; Martin, James G. (Frontiers in Physiology, 2021)
The accumulation of unfolded/misfolded proteins in the endoplasmic reticulum (ER) causes ER stress and induces the unfolded protein response (UPR) and other mechanisms to restore ER homeostasis, including translational shutdown, increased targeting of mRNAs for degradation by the IRE1-dependent decay pathway, selective translation of proteins that contribute to the protein folding capacity of the ER, and activation of the ER-associated degradation machinery. When ER stress is excessive or prolonged and these mechanisms fail to restore proteostasis, the UPR triggers the cell to undergo apoptosis. This review also examines the overlooked role of post-translational modifications and their roles in protein processing and effects on ER stress and the UPR. Finally, these effects are examined in the context of lung structure, function, and disease.